Кеңесбай Рахманов поэзиясында эпифоралардың қолланылыў өзгешеликлери - Кудайбергенова, Г.П (FAN va JAMIYAT, 2025)
This article examines the features of using one type of repetition—epiphora—in linguistics and artistic